RELIABILITY OF PROTECTION OF ELECTROTECHNICAL COMPLEXES - Федорів, Михайло; Курляк, Петро (SWorldJournal, 2022)
The article is devoted to some issues of increasing the reliability of complex electrical systems by means of differential protection. The reliability of protection devices is important, as failure of these devices can cause serious losses. The focus is